A randomized phase 1 single-dose polysomnography study of ASP8062, a GABAB receptor positive allosteric modulator - Mark Walzer; Ruishan Wu; Maha Ahmad; Jon Freeman; Gary Zammit; Gerard J. Marek (Psychopharmacology, 2021)
Rationale Previous research suggests that sleep polysomnography and EEG endpoints can be used to assess GABAergic activity; however, the impact of GABA B receptor positive allosteric modulators on sleep endpoints remains unclear. Objectives This phase 1 study compared a single dose of ASP8062 (35 mg or 70 mg), a GABA B receptor positive allosteric modulator, with placebo and paroxetine (40 mg). Methods Healthy adult volunteers were randomized to four treatments (35 mg ASP8062, 70 mg ASP8062, paroxetine 40 mg, or matching placebo), each separated by a 14-day washout. Primary endpoints obtained by polysomnography were time in stage N3 or SWS and time in rapid eye movement (REM) sleep. Secondary endpoints included impact on sleep stages and electroencephalography parameters, pharmacokinetics, nighttime growth hormone (GH), and safety/tolerability. Results In 20 randomized volunteers, ASP8062 led to a significant and seemingly dose-dependent increase in SWS over the entire night; this increase was mainly observed during the first third of the night. ASP8062 did not impact time in REM sleep. Paroxetine had no effect on SWS but produced a significant reduction in time spent in REM sleep. A dose-dependent trend in increased GH release was also observed with ASP8062. Headache and nausea were the most commonly reported treatment-emergent adverse events (TEAEs) for ASP8062; most TEAEs were mild in severity. Conclusions Single-dose ASP8062 (35 and 70 mg) appeared to result in CNS penetration and enhanced GABAergic activity as measured by increases in slow-wave sleep and growth hormone release.